The Gut Bacteria Dysbiosis Contributes to Chronic Graft-Versus-Host Disease Associated With a Treg/Th1 Ratio Imbalance - Wang, Yulian; Huang, Lisi; Huang, Tian; Geng, Suxia; Chen, Xiaomei; Huang, Xin; Lai, Peilong; Du, Xin; Weng, Jianyu (Frontiers in Microbiology, 2022)
Introduction:Dysbiosis of gut bacteria has been discovered in a large amount of autoimmune diseases. However, the influence of the gut bacteria in mice model of chronic sclerodermatous graft-versus-host disease(Scl-GVHD), a disease resembled autoimmune disease characterized by chronic inflammation of multiple organs, such as skin, etc., remains elusive. Here we explore the role of the gut bacteria in a Scl-cGVHD mice model. Methods:We established a mouse model of Scl-cGVHD, collected fecal flora, analyzed the composition and diversity of intestinal flora using 16S rDNA amplicon sequencing and detected the proportion of Treg and Th1 cells in splenocytes of Scl-cGVHD mice. To verify the immunoregulatory effect of Scl-cGVHD intestinal flora, we prepared bacterial extracts, co-cultured with splenocytes in vitro, and used flow cytometry to detect T cell differentiation and cytokine secretion. Results:By examining T cell differentiation in splenocytes of cGVHD mice, we found that Treg cells were significantly reduced (15.27±0.23 vs 12.23±0.47, P=0.0045) and Th1 cells were increased(1.54±0.18 vs 6.68±0.80, P=0.0034) in cGVHD mice. Significant differences were observed in the composition and diversity of the gut bacteria in mice with Scl-cGVHD versus without GVHD. Analysis of mice fecal bacteria samples(n=10, 5 Scl-cGVHD,5 Non-GVHD）showed that significantly separation(R=0.732, P=0.015, non-parametric analysis(ANOSIM)) in Scl-cGVHD and non-GVHD mice. The abundance of the family and genus Ruminococcaceae bacteria decreased and the family Lachnospiraceae and limited to the species Lachnospiraceae_bacterium_DW17 increased in Scl-cGVHD mice. In vitro, results of celluar level study suggest that the bacteria extracts of gut microbiota from Scl-cGVHD mice modulated the splenic T cells toward to differentiate to the CD4+IFN-γ+ Th1 cells(14.37±0.32 vs 10.40±2.19, P=0.036), and the percentage of CD4+CD25+Foxp3+ tregs decreased(6.36±0.39 vs 8.66±0.07, P=0.001) compared to the non-GVHD mice. In addition, the secretion of proinflammatory IFN-γ cytokine in the supplement of celluar culture was increased(4898.58±235.82 vs 4347.87±220.02 pg/mL,P=0.042) in the mice model of Scl-cGVHD group but the anti-inflammary IL10 decreased(7636.57±608.05 vs 9563.56±603.34pg/mL,P=0.018 ). Conclusions:Our data showed the different composition and diversity of gut bacteria in the Scl-cGVHD mice. The dysbiosis of gut bacteria may regulate the differentiation ratio of Treg and Th1 cells, which was associated with Scl-cGVHD.